Tingkat Kepuasan Pasien dalam Pelayanan Kefarmasian di Puskesmas Bobotsari - Grenita Banowati; Fauziah Fauziah; Silma Kaffah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
This study aims to determine the level of patient satisfaction with pharmaceutical services at the Bobotsari Community Health Center. Patient satisfaction is an important indicator that reflects the quality of healthcare services. This research employed a quantitative descriptive method using a SERVQUAL-based questionnaire, consisting of five dimensions: tangible, reliability, responsiveness, assurance, and empathy. A total of 100 outpatient respondents were selected through accidental sampling. Data were analyzed using descriptive statistics to determine satisfaction scores for each dimension. The results showed that the tangible dimension achieved 80.57% and the reliability dimension achieved 82%, both categorized as very satisfied. Meanwhile, responsiveness (79.02%), assurance (79.05%), and empathy (77.95%) were categorized as satisfied. The overall average satisfaction level was 79.72%, indicating that patients were generally satisfied with the pharmaceutical services. However, several aspects such as service speed, communication clarity, and personal attention from staff still require improvement. The findings emphasize the importance of maintaining service quality to achieve better patient experiences and public trust.